Direct synthesized graphene-like film on SiO₂: Mechanical and optical properties - Bortchagovsky, E.G.; Vasin, A.V.; Lytvyn, P.M.; Tiagulskyi, S.I.; Slobodian, A.M.; Verovsky, I.N.; Strelchuk, V.V.; Stubrov, Yu.; Nazarov, A.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Exploiting CVD technique for carbon deposition from C₂H₂+H₂+N₂ mixture, a graphene-like film synthesized directly on SiO₂ surface of SiO₂-Si structure was obtained. The graphene-like film was grown under thin Ni layer that is easy exfoliated from graphene-SiO₂-Si structure. Surface of the film was sufficiently smooth and reveals no winkles and holes; it has a good homogeneity and perfect adhesion to SiO₂ layer. Studying the micro-Raman spectra showed a graphene-like structure of the film; using atomic force microscopic technique, the thickness of film was determined (0.6 nm). Using spectroscopic ellipsometry and simple Cauchy model enabled us to estimate optical parameters of this graphene-like film.